Contribuição de silício e alumínio na gênese do caráter coeso - Paula, Nathielly Herculano de (2018)
The Coastal Tracks are a geomorphological unit formed from the continental sediments, deposited by interlaced fluvial systems and associated to alluvial fans, these sediments make up the so-called Barreiras Formation, present in part of the Brazilian coast. Soils of this region present peculiar characteristics, such as the appearance of horizons with strong and temporary cohesion, called horizons with cohesive character. The genesis of this horizon is still little known, some experiments have shown that its formation may be influenced by compounds of low crystallinity that, under a prolonged regime of wetting and drying cycles, accumulate forming horizon with strong cohesion. For this reason, the objective of the study was to verify if silicon and aluminum under the influence of the wetting and drying cycles contribute to the cohesion in soils of the Coastal Trays. For this, the compounds of low crystallinity of a horizon with cohesive character with ammonium oxalate were extracted, and then saturations with solutions of silicic acid (H4SiO4) and aluminum chloride (AlCl3), respectively, under three levels of cycles of wetting and drying: 10, 20 and 30 times. A completely randomized design with factorial was used. The evaluation was performed by measurements of penetration resistance (Rp), soil density (Ds), hydraulic conductivity of the saturated soil (Ksat), soil permeability to air (Kar). Data were submitted to analysis of variance (ANOVA), Tuckey test at a significance level of 5%. It was observed that silicon (Si) contributed to the increase in Rp values and reduction in soil hydraulic conductivity and soil permeability to air and that the number of wetting and drying cycles did not influence the values found for the parameters Ds, Rp, Ksat, Kar, in addition, the Si and Al contents in the Si + Al treatment indicate that there is interaction between these elements, and there may be some aluminosilicate compound that favors the increase of the values of the evaluated parameters.